2013
DOI: 10.3892/mmr.2013.1264
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity reaction studies of a polyethoxylated castor oil-free, liposome-based alternative paclitaxel formulation

Abstract: The commercial drug paclitaxel (Taxol) may introduce hypersensitivity reactions associated with the polyethoxylated castor oil-ethanol solvent. To overcome these problems, we developed a polyethoxylated castor oil-free, liposome-based alternative paclitaxel formulation, known as Lipusu. In this study, we performed in vitro and in vivo experiments to compare the safety profiles of Lipusu and Taxol, with special regard to hypersensitivity reactions. First, Swiss mice were used to determine the lethal dosages, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…Materials Calix [6] arene, calix [8] arene, and PTX were purchased from TCI (Shanghai, China). Ethyl chloroacetate (99%), pyrene (99%), Tween 80 (pharmaceutical grade) were obtained from Aladdin Reagent (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Materials Calix [6] arene, calix [8] arene, and PTX were purchased from TCI (Shanghai, China). Ethyl chloroacetate (99%), pyrene (99%), Tween 80 (pharmaceutical grade) were obtained from Aladdin Reagent (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…The tetracarboxylic acid of p-tert-butylcalix [4] arene introduced by Ungaro and colleagues was an early example of a water-soluble calixarene. 21) Shinkai et al reported the preparation of p-sulfonato calix [6] arene. 22) Other anionic water-soluble derivatives containing nitro, 23) phosphonic acid, 24) and carboxyl 25) moieties emerged, and the first example of a cationic water-soluble calixarene was reported by Shinkai et al 26) Other cationic calixarenes contain tetraalkylammonium groups and primary amines.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Supraventricular arrhythmias, including atrial fibrillation, atrial flutter, and atrial tachycardias, have also occurred with taxanes. 79,81,82 Although the pathogenesis of these arrhythmias may be multifactorial, studies implicate paclitaxel drug delivery vehicle (polyethoxylated castor oil) inducing histamine release as another precipitating factor. 79,81,82 Paclitaxel, similar to colchicine, is microtubule-stabilizing agent, and in normal postmitotic cardiomyocytes, microtubule density is low; thus, taxane agents are not thought to hinder cardiomyocyte contraction.…”
Section: Microtubule Inhibitorsmentioning
confidence: 99%